Literary Criticism of Cross-Class Marriage in the Novel Heart of the Night Dialectical Perspective of George Wilhelm Friedrich Hegel - Tjalau, Cutri; R. Saleh, Sriwahyuningsih (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
This study aims to analyze cross-class marriage in the novel